The political economy of ownership: housing markets and the welfare state - Benjamin Ansell (Cambridge University Press, 2014)
The major economic story of the last decade has been the surge and collapse of house prices worldwide. Yet political economists have had little to say about how this critical phenomenon affects citizens’ welfare and their demands from government. This article develops a novel theoretical argument linking housing prices to social policy preferences and policy outcomes. I argue that homeowners experiencing house price appreciation will become less supportive of redistribution and social insurance policies since increased house prices both increase individuals’ permanent income and the value of housing as self-supplied insurance against income loss. Political parties of the right will, responding to these preferences, cut social spending substantially during housing booms. I test these propositions using both microdata on social preferences from panel surveys in the USA, the UK, and a cross-country survey of 29 countries, and macrodata of national social spending for 18 countries between 1975 and 2001.